2004
DOI: 10.2337/diabetes.53.10.2581
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Role of B-Cells in Type 1 Diabetes in the NOD Mouse

Abstract: B-cells are important in the development of type 1 diabetes, but their role is not completely defined. Although B-cells produce autoantibodies, these are not thought to be pathogenic; however, their antigen-presenting function is postulated to be critical. To examine the relative importance of these functions of B-cells, we have generated nonobese diabetic (NOD) B-cell-deficient mice that express a transgene encoding a mutant heavy chain immunoglobulin transgene on the cell surface but cannot secrete immunoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
176
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(182 citation statements)
references
References 42 publications
6
176
0
Order By: Relevance
“…Previous studies have highlighted the importance of B cells as antigen-presenting cells in the pathology of diabetes [5,24,28,29]. Our work demonstrates that peritoneal B cells are indeed capable of triggering a T cell response.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have highlighted the importance of B cells as antigen-presenting cells in the pathology of diabetes [5,24,28,29]. Our work demonstrates that peritoneal B cells are indeed capable of triggering a T cell response.…”
Section: Discussionsupporting
confidence: 61%
“…B cells can bind antigen with high affinity and are more effective than dendritic cells and macrophages at capturing and presenting rare antigens (39,40). An impact of B cells via antigen presentation and T cell priming and/or expansion has been invoked to explain the B-cell dependence of autoimmune diabetes in the NOD mouse (16,41), although more recently it was suggested that B cells in this context might also play a role in controling regulatory T cells (21), which may or may not be a reflection of the same molecular process(es). Our results in the AireϪ/Ϫ setting are consistent with an effect of B cells on the priming/expansion of autoreactive T lymphocytes: T cells alone can transfer multiorgan autoimmunity in an effector phase that appears to be B-cell independent.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that T-cell epitopes often occur close to B-cell epitopes, for both extrinsic and autoantigens (28), directs attention to the role of B-cells in modulating T-cell responses (29 -34). In antigen-presenting cells, antigen-antibody complexes can remain intact after the internalization and fragmentation by proteases along the antigen-processing pathway (32,33), thus protecting residues from proteolysis and modulating presentation of peptides and ensuing T-cell responses. Studies on B-cell modulation of the T-cell response to GAD65 indicate that B-cell clones producing mAbs DPA and DPD (but not DPC) can present the T1 (residues 115-130), T2 (residues 270 -283), and T5 (residues 556 -575) peptide epitope sequences to DRB1*0401-restricted T-cell clones (30).…”
Section: Discussionmentioning
confidence: 99%